Kindergarten Resource Pack Understanding the World - The City School (Lahore : The City School)
Understanding the World" resource pack for kindergarten introduces young learners to their environment, focusing on community, seasons, plants, and animals. It includes engaging, hands-on activities that promote curiosity and exploration. This pack fosters awareness of cultural diversity and encourages social interaction among students.
Location: 1B
Keywords: Textbook